Examining The Relationship Between Economic, Demographic, Legal And Institutional Variables Towards Tax Evasion : A Case Study In West Kalimantan - Felicia Kiki Simanjaya; Elok Heniwati (Educoretax, 2023)
Tax evasion, one of the most common crimes in the world. There are so many cases of tax evasion that are not known by the public, in fact there are many cases of tax evasion that are closed and only revealed a few years later. This is also happened in Indonesia. Without exception, Indonesia is also one of the countries with the most tax evasion practices. To examine which factor, affect the tax evasion practice the most, this problem needs to be studied further. This research aims to examine and reveals how the economic variable, demographic variable, and legal and institutional variable affect tax evasion practice with West Kalimantan, Indonesia as the studied area. This research uses the multiple regression analysis as its research method. Questionnaire was used for the data collection where the questionnaire succeeded to obtain 120 respondents as research population, then 100 sample gained after screening process . The result of this research is that the economic variable and the legal and institutional variable has a positive effect on tax evasion practice and the demographic variable has a negative effect on tax evasion practice.